Effects of In Situ Electrical Pulse Treatment on the Microstructure and Mechanical Properties of Al-Zn-Mg-Cu Alloy Resistance Spot Welds - Shitian Wei; Xiaoyu Ma; Jiarui Xie; Yali Xie; Yu Zhang (Metals, 2025)
This study introduces a novel in situ pulsed current-assisted resistance spot welding method, which differs fundamentally from conventional post-weld heat treatments and is designed to enhance the mechanical performance of 7075-T651 aluminum alloy joints. Immediately after welding, a short-duration pulsed current is applied while the weld remains in a high excess-vacancy state, effectively accelerating precipitation reactions within the weld region. Transmission electron microscopy (TEM) observations reveal that pulsed current treatment promotes the formation of band-like solute clusters, indicating a significant acceleration of the early-stage precipitation process. Interestingly, the formation of quasicrystalline phases—rare in Al-Zn-Mg-Cu alloy systems—is incidentally observed at grain boundaries, exhibiting characteristic fivefold symmetry. Selected area electron diffraction (SAED) patterns further show that these quasicrystals undergo partial dissolution under the influence of the pulsed current, transforming into short-range ordered cluster-like structures. Lap shear tests demonstrate that joints treated with pulsed current exhibit significantly higher peak load and energy absorption compared to untreated specimens. Statistical analysis of weld size confirms that both groups possess comparable weld diameters under identical welding currents, suggesting that the observed mechanical improvements are primarily attributed to microstructural evolution rather than geometric factors.